Preliminary Study of Poly(Tetrahydrofurfuryl Acrylate) Thin Film as a Potential Material of Ion Selective Electrodes: The Case of Nitrate Ion-Selective Electrode - Sagir Alva; Robi Suherman; Vivi Friliandita; Deni Shidqi Khaerudini; Edy Herianto Majlan; Aiman Sajidah Abd Aziz (Universitas Gadjah Mada, 2020)
A preliminary study on the use of a photocurable poly-tetrahydrofurfuryl acrylate (pTHFA) has been successfully performed as an alternative membrane for application in the Ion-Selective Electrode (ISE) sensors such as Nitrate-ISE. The pTHFA membrane was synthesized using photopolymerization technique and further optimized by varying the concentration of the photo-initiator. The pTHFA photopolymer was characterized by C-NMR, H-NMR, FTIR, and DSC. The best sensing formulation comprising pTHFA photopolymer was obtained from composition II with Tg of -17.3 °C. In the Nitrate-ISE fabrication process, initially, the tetraoctylammonium nitrate (TOAN) ionophore was optimized. The optimum TOAN concentration of 4.2 mg was then immobilized onto composition II as a sensing matrix. Results showed that the pTHFA based ISE sensor exhibited a slope near the Nernstian number with a good linear response for detecting nitrate ion concentration between 10–1 to 10–4 M (r2 = 0.9994) and limit of detection as low as 3.47 × 10–5 M. Furthermore, the selectivity behavior of pTHFA based nitrate-ISE sensor was determined in various types of interfering ions such as SO42–, H2PO4–, HPO42–, Cl– and I–. The sensor has demonstrated selectivity coefficient of -2.27 ± 0.2, -2.49 ± 0.6, -2.18 ± 0.8, -1.31 ± 0.1 and 0.41 ± 0.2, respectively. The fabricated pTHFA ISE-Nitrate sensor was further tested in the fish ponds, soils, and also rivers. The sensors have shown excellent performance and is comparable to the standard method.